2000
DOI: 10.1109/91.868949
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of fuzzy thresholding-based buffer management for a large-scale cell-switching network

Abstract: This paper addresses three key issues in buffer management in cell switching networks including asynchronous transfer mode (ATM) networks. First, it develops a model of fuzzy thresholding-based buffer management for a 50-switch representative cell-switching network, to study its performance under realistic conditions. Previous studies have been confined to a single switch and, consequently, the results are not necessarily applicable to a real-world cell-switching network consisting of multiple switches. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The exact units of the quantities in the above equation will depend on the network under consideration. Estimates of 't' may be obtained through sophisticated modeling and simulation [18].…”
Section: A Definition Of High-speed Networkmentioning
confidence: 99%
“…The exact units of the quantities in the above equation will depend on the network under consideration. Estimates of 't' may be obtained through sophisticated modeling and simulation [18].…”
Section: A Definition Of High-speed Networkmentioning
confidence: 99%
“…In this study, ATMSIM 1.0 is executed on a testbed of Pentium laptops, configured under the Linux operating system and interconnected through a 100 Mb/s Fast Ethernet. While ATMSIM 1.0 incorporates input traffic [16,17], designed to emulate a representative ATM network, it permits users to generate call SETUP requests externally and insert them into the network. Traffic consists of audio, video, and data.…”
Section: 2mentioning
confidence: 99%
“…The fuzzy buffer management technique utilizes an asymmetric "sigmoid" membership function from which fuzzy threshold values are determined corresponding to the discrete buffer occupancy levels [3] [4], and for the fixed thresholding scheme, the admission policy is encapsulated by the equation:…”
Section: Performance Analysis Of Adbm Number Of Cells Interceptedmentioning
confidence: 99%
“…They proposed the use of fuzzy thresholds and comparative analysis on a representative, large-scale, ATM network [4] revealed that this approach adapts superbly to sharp changes in cell arrival rates and maximum burstiness of bursty traffic sources. Under this approach, the threshold is adjusted continuously to reflect the dynamic state of the buffer.…”
Section: Introductionmentioning
confidence: 99%